The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1103/physrevb.82.075421
|View full text |Cite
|
Sign up to set email alerts
|

Water-induced surface reconstruction of oxygen(2×1)covered Ru(0001)

Abstract: Low-temperature scanning tunneling microscopy and density-functional theory ͑DFT͒ were used to study the adsorption of water on a Ru͑0001͒ surface covered with half monolayer of oxygen. The oxygen atoms occupy hcp sites in an ordered structure with ͑2 ϫ 1͒ periodicity. DFT predicts that water is weakly bound to the unmodified surface, 86 meV compared to the ϳ200 meV water-water H bond. Instead, we found that water adsorption causes a shift of half of the oxygen atoms from hcp sites to fcc sites, creating a hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The diffusion rate drops to <0.01 s −1 at 250 K and order 10 −5 s −1 at 200 K. This suggests that the surface oxygen layer is unlikely to equilibriate over experimental time periods at temperatures of much less than room temperature. This confirms that a lack of surface oxygen mobility is the reason that equilibrium defect concentrations expected for around 200−300 K were observed on STM conducted at 7 K. 16 3.3. Formamide Adsorption to a Ru (0001) Surface with Perfectly Ordered Oxygen Overlayer.…”
Section: Resultssupporting
confidence: 85%
“…The diffusion rate drops to <0.01 s −1 at 250 K and order 10 −5 s −1 at 200 K. This suggests that the surface oxygen layer is unlikely to equilibriate over experimental time periods at temperatures of much less than room temperature. This confirms that a lack of surface oxygen mobility is the reason that equilibrium defect concentrations expected for around 200−300 K were observed on STM conducted at 7 K. 16 3.3. Formamide Adsorption to a Ru (0001) Surface with Perfectly Ordered Oxygen Overlayer.…”
Section: Resultssupporting
confidence: 85%
“…1,6,54−56 At higher O coverage, when all top sites are blocked, water adsorption causes a shift of half of the oxygen atoms from hcp sites to fcc sites, creating a honeycomb structure where water molecules bind strongly to the exposed Ru atoms. 6 The energy cost of reconstructing the oxygen overlayer is more than compensated by the larger adsorption energy of water on the newly exposed Ru atoms.…”
Section: ■ Water−oxygen Interaction: From Coadsorbed Oxygen To Oxidesmentioning
confidence: 99%
“…Many coadsorption studies have been carried out with traditional surface science techniques, in particular water coadsorbed with alkalis, O, and CO. 10 On Ru(0001), preadsorbed oxygen was found to result in a stronger binding of H 2 O, owing to the formation of hydrogen bonds between the molecule and the chemisorbed oxygen. 1,6,53,54 At the same time, the surface oxygen changes the chemical state of adsorbed water through strong H-bonding and can promote water dissociation. 55,56 STM and XPS experiments have shown that the presence of oxygen vacancies in the O(2 × 2)/Ru(0001) is necessary for H 2 O dissociation to occur.…”
Section: ■ Water−oxygen Interaction: From Coadsorbed Oxygen To Oxidesmentioning
confidence: 99%
“…In contrast, Kolb et al [47] observed that water remains intact on (111) honeycomb structure such that water molecules bind strongly to the exposed Ru atoms. [54] DFT revealed that the energy cost of reconstructing the oxygen overlayer is more than compensated by the adsorption energy of water on the newly exposed Ru atoms.…”
Section: Formation Of the First Water Layermentioning
confidence: 99%